Prepositions (Huruf Al-Jar): Addition, Deletion And Attachment To The Infinitives (Al-Afaal Al-Mujarradah) In The Arabic Sentence - Mulaiha Mohammad Zaaf Al-Qahtani (Ijaz Arabi Journal of Arabic Learning, 2023)
The Arabic language's prepositions (huruf al-jarr) are among the letters specific to nouns, and they are most likely 20 letters. The present research deals with the ‘huruf al-jarr’ (prepositions) used in Arabic sentences regarding their addition and deletion from some Arabic sentences assuming the hidden or implied words. Also, the research deals with attaching the prepositions to the infinitives (al-afaal al-mujarradah) and its impact on the meaning and significance. Moreover, according to the objectives, the research will address the issue of adding the ‘huruf al-jarr,' the purpose behind the addition, the places from where the ‘huruf al-jarr’ is deleted, how the deleted item will be assumed and what is the effect of attaching these prepositions to the infinitives in some sentences of the Arabic language. The research relied on the descriptive analytical approach as it is appropriate for the study. The study's main results reveal that the actual particle (al-Harf al-Asli) must produce a new meaning that did not exist before its addition to the sentence. In contrast, the other particle (al-harf al-zaaid) only strengthens the general meaning of the sentence without producing a new meaning. Additionally, the actual particle and its associated noun must be related to an "aamil" to complete its meaning and deliver its effect to the noun in the genitive case (al-ism al-majroor). In contrast, the other particle does not need an "aamil" relation. Lastly, the actual particle causes the following noun to be in the genitive case, with no other place of declension (al-eraab) for itself or the following words. In contrast, the other particle requires an area of declension (al-eraab).